(untitled) (The Macau Ricci Institute Journal, 2022)
Giuseppe Castiglione, arrived in China during one of the most troubled times in history, in the midst of the Rites Controversy. Yet, he came to know the interiority of the Qianlong emperor with deep intimacy. His design work at the Yuanmingyuan reflects an empathic understanding of the Emperor’s desires and longings, emulating the spiritual unity of the Lord Creator with artists and architects working as one. Having known Qianlong since the Emperor’s childhood, he was well aware of his pleasures and concerns, his self perception as Son of Heaven, and Lord of the vast domain he held together in an era of peace. Castiglione and his Jesuit brethren gathered inspiration from the creative design of gardens and palaces from their imaginative memory and the similar lived experience of the most powerful figures in Europe. Parallels are drawn between Maria de Medici’s longing for her home in Florence articulated in the design of Luxembourg garden and the emperor’s desire to quell the longing of his Fragrant Concubine, Xiang Fei, for her home in Kashgar shown in the Islamic influences found the Belvedere palace at Yuanmingyuan. Marian imagery in the depiction of the Emperor’s concubine waiting for her Lord is also examined. The spiritual lesson: in times of crisis, speak less, listen more and engage your senses.